Factors influencing customer satisfaction using e-hailing services in Melaka - Ahmad Fadzil, Mohamad (2021)
E-hailing applications systems have resulted in increased competition between, and the greater availability of, taxis and drivers on the market in many cities. Among these systems, GrabCar has been favored by citizens of Malaysia, based on an online survey conducted by the Land Public Transport Commission (SPAD). However, limited numbers of studies in Malaysia have investigated customer satisfaction with ride-hailing applications. No studies specifically focus on ride-sharing apps, such as GrabCar, in Melaka state. Hence, the aim of this study is to examine the factors of using e-hailing services in terms of customer satisfaction in Melaka. This involved determining three relationships, which are the relationship between perceived ease of use and customer satisfaction; the relationship between perceived usefulness and customer satisfaction; and the relationship between security and privacy and customer satisfaction with e-hailing services in Melaka. The research study was conducted in the Central Melaka District with an estimated sample size of 381 respondents. Descriptive analysis and Multiple Regression Analysis (MRA) were carried out to test the hypotheses suggested and determine the most influential factors to include in the research model. Based on the analysis results, the three independent variables - perceived ease of use, perceived usefulness and security and privacy - positively affect customer satisfaction. Therefore, all the hypotheses were accepted and all the significant factors were implemented in the research model. The findings are valuable to the management of any e-hailing organization, as they might be used to enhance levels of user satisfaction with e-hailing services, especially in tourist regions such as Melaka.